(untitled) (Revista Contexto & Educação, 2026)
This paper analyzes the therapeutic process of an eleven-year-old child living in an institutional care setting, treated at a Child and Adolescent Psychosocial Care Center (CAPSi) in the metropolitan region of Porto Alegre, Brazil. To preserve her identity, the child is referred to by the pseudonym “Violet.” The study was developed using a case study methodology, based on clinical follow-up, highlighting singular and contextual aspects of the case. The initial demand involved intense emotional episodes and behaviors marked by outbursts of anger within the institutional environment. Institutional placement resulted from situations of family violence, neglect, and abandonment, leading to Violet’s separation from her younger siblings. At the beginning of treatment, the child presented intense psychological distress, significant difficulties in forming bonds, and feelings of insecurity associated with the interruption of the maternal relationship. In the context of abandonment, Violet was overburdened by the early need to care for herself, becoming highly susceptible to environmental stimuli. Within the therapeutic setting, storytelling emerged as a central clinical resource, fostering psychic elaboration and the symbolic representation of the experienced suffering. Literary narratives enabled the child to attribute meaning to her experiences, promoting symbolization, verbal expression, and the construction of a personal narrative through identification with characters and plots. Throughout the therapeutic process, a strengthening of the therapeutic bond and a progressive expansion of Violet’s symbolic and expressive capacities were observed. It is concluded that literature, as a clinical resource, symbolically enriches the psychotherapeutic process and produces significant effects on the elaboration of childhood psychological suffering.